Association of miRNA biosynthesis genes DROSHA and DGCR8 polymorphisms with cancer susceptibility: a systematic review and meta-analysis. Issue 3 (27th June 2018) - Wen, Jing; Lv, Zhi; Ding, Hanxi; Fang, Xinxin; Sun, Mingjun
Abstract : Single nucleotide polymorphisms (SNPs) in miRNA biosynthesis genes DROSHA and DGCR8 were indicated to be correlated with cancer risk. We comprehensively reviewed and analyzed the effect of DROSHA and DGCR8 polymorphisms on cancer risk. Eligible articles were selected according to a series of inclusion and exclusion criteria. Consequently, ten case–control studies (from nine citations) with 4265 cancer cases and 4349 controls were involved in a meta-analysis of seven most prevalent SNPs (rs10719 T/C, rs6877842 G/C, rs2291109 A/T, rs642321 C/T, rs3757 G/A, rs417309 G/A, rs1640299 T/G). Our findings demonstrated that the rs417309 SNP in DGCR8 was significantly associated with an elevated risk of overall cancer in every genetic model. In stratified analysis, correlations of DROSHA rs10719 and rs6877842 SNPs were observed in Asian and laryngeal cancer subgroups, respectively. Moreover, associations of the rs417309 SNP could also be found in numerous subgroups including: Asian and Caucasian population subgroups; laryngeal and breast cancer subgroups; population-based (PB) and hospital-based (HB) subgroups. In conclusion, the DROSHA rs10719, rs6877842 SNPs, and DGCR8 rs417309 SNP play pivotal roles in cancerogenesis and may be potential biomarkers for cancer-forewarning.